Nanocrystalline Fe-Fe2O3 particle-deposited N-doped graphene as an activity-modulated Pt-free electrocatalyst for oxygen reduction reaction - Dhavale, Vishal M.; Singh, Santosh K.; Nadeema, Ayasha; Gaikwad, Sachin S.; Kurungot, Sreekumar (Nanoscale, 2015)
The size-controlled growth of nanocrystalline Fe-Fe2O3 particles (2-3 nm) and their concomitant dispersion on N-doped graphene (Fe-Fe2O3/NGr) could be attained when the mutually assisted redox reaction between NGr and Fe3+ ions could be controlled within the aqueous droplets of a water-in-oil emulsion. The synergistic interaction existing between Fe-Fe2O3 and NGr helped the system to narrow down the overpotential for the oxygen reduction reaction (ORR) by bringing a significant positive shift to the reduction onset potential, which is just 15 mV higher than its Pt-counterpart. In addition, the half-wave potential (E-1/2) of Fe-Fe2O3/NGr is found to be improved by a considerable amount of 135 mV in comparison to the system formed by dispersing Fe-Fe2O3 nanoparticles on reduced graphene oxide (Fe-Fe2O3/RGO), which indicates the presence of a higher number of active sites in Fe-Fe2O3/NGr. Despite this, the ORR kinetics of Fe-Fe2O3/NGr are found to be shifted significantly to the preferred 4-electron-transfer pathway compared to NGr and Fe-Fe2O3/RGO. Consequently, the H2O2% was found to be reduced by 78.3% for Fe-Fe2O3/NGr (13.0%) in comparison to Fe-Fe2O3/RGO (51.2%) and NGr (41.0%) at -0.30 V (vs. Hg/HgO). This difference in the yield of H2O2 formed between the systems along with the improvements observed in terms of the oxygen reduction onset and E-1/2 in the case of Fe-Fe2O3/NGr reveals the activity modulation achieved for the latter is due to the coexistence of factors such as the presence of the mixed valancies of iron nanoparticles, small size and homogeneous distribution of Fe-Fe2O3 nanoparticles and the electronic modifications induced by the doped nitrogen in NGr. A controlled interplay of these factors looks like worked favorably in the case of Fe-Fe2O3/NGr. As a realistic system level validation, Fe-Fe2O3/NGr was employed as the cathode electrode of a single cell in a solid alkaline electrolyte membrane fuel cell (AEMFC). The system could display an open circuit voltage (OCV) of 0.73 V and maximum power and current densities of 54.40 mW cm(-2) and 200 mA cm(-2), respectively, which are comparable to the performance characteristics of a similar system derived by using 40 wt% Pt/C as the cathode electrode.

Surface-tuned Co3O4 nanoparticles dispersed on nitrogen-doped graphene as an efficient cathode electrocatalyst for mechanical rechargeable zinc-air battery application - Singh, Santosh K.; Dhavale, Vishal M.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
The most vital component of the fuel cells and metal air batteries is the electrocatalyst, which can facilitate the oxygen reduction reaction (ORR) at a significantly reduced overpotential. The present work deals with the development of surface-tuned cobalt oxide (Co3O4) nanoparticles dispersed on nitrogen-doped graphene as a potential ORR electrocatalyst possessing some unique advantages. The thermally reduced nitrogen-doped graphene (NGr) was decorated with three different morphologies of Co3O4 nanoparticles, viz., cubic, blunt edged cubic, and spherical, by using a simple hydrothermal method. We found that the spherical Co3O4 nanoparticle supported NGr catalyst (Co3O4-SP/NGr-24h) has acquired a significant activity makeover to display the ORR activity closely matching with the state-of-the-art Pt supported carbon (PtC) catalyst in alkaline medium. Subsequently, the Co3O4-SP/NGr-24h catalyst has been utilized as the air electrode in a Zn-air battery, which was found to show comparable performance to the system derived from PtC. Co3O4-SP/NGr-24h catalyst has shown several hours of flat discharge profile at the discharge rates of 10, 20, and 50 mA/cm(2) with a specific capacity and energy density of similar to 590 mAh/g(-zn) and,840 Wh/kg(-zn), respectively, in the primary Zn-air battery system. In conjunction, Co3O4-SP/NGr-24h has outperformed as an air electrode in mechanical rechargeable Zn-air battery as well, which has shown consistent flat discharge profile with minimal voltage loss at a discharge rate of 50 mA/cm(2). The present results, thus demonstrate that the proper combination of the tuned morphology of Co3O4 with NGr will be a promising and inexpensive material for efficient and ecofriendly cathodes for Zn-air batteries.
Keywords: electrocatalyst; mixed facets; oxygen reduction reaction; rechargeable zinc-air battery; surface morphology

Switching closed-shell to open-shell phenalenyl: toward designing electroactive materials - Pariyar, Anand; Vijaykumar, Gonela; Bhunia, Mrinal; Dey, Suman Kr.; Singh, Santosh K.; Kurungot, Sreekumar; Mandal, Swadhin K. (Journal of the American Chemical Society, 2015)
Open-shell phenalenyl chemistry started more than half a century back, and the first solid-state phenalenyl radical was realized only 15 years ago highlighting the synthetic challenges associated in stabilizing carbon-based radical chemistry, though it has great promise as building blocks for molecular electronics and multifunctional materials. Alternatively; stable closed-shell phenalenyl has tremendous potential as it can be utilized, to create an in situ open-shell state by external spin injection. In the present study, we have designed a closed-shell phenalenyl-based iron(III) complex, Fe-III(PLY)(3) (PLY-H = 9-hydroxyphenalenone) displaying an excellent electrocatalytic property as cathode material for one compartment membraneless H2O2 fuel cell. The power density output Of Fe-III(PLY)(3) is nearly 15-fold higher than the structurally related model compound Fe-III(acac)(3) (acac = acetylacetonate) and nearly 140-fold higher than an earlier reported mononuclear Fe(III) complex; Fe-III(Pc)Cl (Pc = pthalocyaninate), highlighting the role of switchable closed-shell phenalenyl moiety for electron-transfer process in designing electroactive materials.

10000-Fold enhancement in proton conduction by doping of cesium ions in a proton-conducting zwitterionic metal-organic framework - Shalini, Sorout; Aggarwal, Shubhangi; Singh, Santosh K.; Dutt, Malvika; Ajithkumar, Thallaseril G.; Vaidhyanathan, Ramanathan (European Journal of Inorganic Chemistry, 2016)
Developing metal-organic framework (MOF)-based proton-conducting electrolytes for fuel-cell applications is an important target that has drawn a lot of attention. A key approach involves the selective replacement of the guest species within the pores to enhance performance. The modular and crystalline nature of the MOF permits controlled introduction of such species and characterization of their compositions with high precision, a task which is very difficult to achieve in amorphous polymers. Herein, we partially replaced the protons of a zwitterionic pyridinol in Mg(terephthalate)(pyridinol) MOF 1 with Cs+ ions, which brought about a 10000-fold increase in the proton conductivity (10(-6) to 10(-2) S cm(-1)). Interestingly, Li+ ions could not be loaded, whereas Cs+ ions with smaller hydrated ionic radii could be loaded, and the loading was controlled as a function of time. The Cs+ loading nearly halved the activation energy (from 0.35 for 1 to 0.19 eV for _Cs). The highest conductivities were realized for an optimal loading of Cs+ ions, which was found to be about 10 % in this case.

Coordination polymers of Fe(III) and Al(III) ions with TCA ligand: distinctive fluorescence, CO2 uptake, redox-activity and oxygen evolution reaction - Dhara, Barun; Sappati, Subrahmanyam; Singh, Santosh K.; Kurungot, Sreekumar; Ghosh, Prasenjit; Ballav, Nirmalya (Dalton Transactions, 2016)
Fe and Al belong to different groups in the periodic table, one from the p-block and the other from the d-block. In spite of their different groups, they have the similarity of exhibiting a stable 3+ oxidation state. Here we have prepared Fe(III) and Al(III) based coordination polymers in the form of metal-organic gels with the 4,4', 4 `'-tricarboxyltriphenylamine (TCA) ligand, namely Fe-TCA and Al-TCA, and evaluated some important physicochemical properties. Specifically, the electrical conductivity, redox-activity, porosity, and electrocatalytic activity (oxygen evolution reaction) of the Fe-TCA system were noted to be remarkably higher than those of the Al-TCA system. As for the photophysical properties, almost complete quenching of the fluorescence originating from TCA was observed in case of the Fe-TCA system, whereas for the Al-TCA system a significant retention of fluorescence with red-shifted emission was observed. Quantum mechanical calculations based on density functional theory (DFT) were performed to unravel the origin of such discriminative behaviour of these coordination polymer systems.

Pb2+-N bonding chemistry: recycling of polyaniline-pb nanocrystals waste for generating high-performance supercapacitor electrodes - Jha, Plawan Kumar; Singh, Santosh K.; Gatla, Suresh; Mathon, Olivier; Kurungot, Sreekumar; Ballav, Nirmalya (Journal of Physical Chemistry C, 2016)
Understanding of Pb-N bonding chemistry is not only fundamentally important in the view of relativistic inert-pair effect but also is important for therapeutic as well as environmental applications. In the present study, an unusual reactivity of N-containing pi-conjugated polyaniline emeraldine base (EB) toward aqueous Pb2+ ions has been identified. In the course of sequestering Pb2+ ions by EB, cuboid-shaped nanocrystals were isolated. Synchrotron-based X-ray absorption near-edge structure and extended X-ray absorption fine structure techniques were employed to understand Pb-N bonding chemistry in EB-Pb nanocrystals. The adopted methodology of slow exposure of HCl vapor to EB-Pb nanomaterial facilitated the isolation of polyaniline emeraldine-salt (ES) with unique morphological patterns, porosity and electrical conductivity. The electrochemical device based on recycled ES showed high-capacitance value (similar to 606 F/g @1 A/g and similar to 663 F/g @10 mV/s), high-energy density (similar to 14.8 Wh/kg at power density of similar to 663 W/kg) and excellent-cycling stability (only similar to 15% degradation after 1100 continued cycles at current density of 5 A/g). Notably, ES materials prepared directly from EB and upon exposing HNO3 vapor exhibited greatly inferior device performance.

Reduced graphene oxide modified electrodes for sensitive sensing of gliadin in food samples - Chekin, Fereshteh; Singh, Santosh K.; Vasilescu, Alina; Dhavale, Vishal M.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (ACS Sensors, 2016)
Incidences of food allergies are on the rise, which can greatly affect the well-being of children as well as adults. Intolerance to gluten, a protein composite of gliadin and glutenin, present in wheat, barley, and rye and several cereals, can be the causative agent of celiac disease (CD) and other allergic reactions. A gluten-free diet has become essential for people affected by CD, and consequently, the amount of gluten in food products needs to be strictly controlled. In this paper, we report an electrochemical label-free immunosensor for ultrasensitive and specific detection of gliadin. The sensor takes advantage of the specific properties of porous reduced graphene oxide (prGO) covalently functionalized with anti-gliadin antibodies using 1-pyrenecarboxylic acid as linker molecule. Using differential pulse voltammetry (DPV) and [Fe(CN)6](3-/4-) as a redox probe, a decrease of current is linked to the presence of gliadin. The sensor achieved a detection limit of 1.2 ng mL(-1) over a 1.2-34 ng mL(-1) linear range with high selectivity. The advantages offered by this sensor are the possibility to regenerate the surface of the immunosensor, its rapid and ease of production, as well as applicability for the screening of gliadin concentrations in real food samples, as shown here.
Keywords: anti-gliadin antibody; food samples; gliadin; Immunosensor; Porous reduced graphene oxide

Strategic Preparation of Efficient and Durable NiCo Alloy Supported N-Doped Porous Graphene as an Oxygen Evolution Electrocatalyst: A Theoretical and Experimental Investigation - Singh, Santosh K.; Kumar, Deepak; Dhavale, Vishal M.; Pal, Sourav; Kurungot, Sreekumar (Advanced Materials Interfaces, 2016)
Development of an efficient and durable water splitting electrocatalyst holds a great commitment for the future energy devices. The real application of oxygen evolution reaction (OER) catalysts mainly suffers from sluggish kinetics and high overpotential except for the Ir and Ru-based systems. However, the high cost and vulnerability of the Ir and Ru metals are the main hostiles to use them for marketization. Herein, a high-performance OER electrocatalyst consisting of NiCo alloy nanoparticles supported on high surface area N-doped porous graphene (NiCo/pNGr(75: 25)) is reported. The importance of the doped-N for achieving the uniform dispersion-cum-effective interaction of the size controlled NiCo alloy nanoparticles has been explicitly investigated by transmission electron microscopy, X-ray diffraction, X-ray photo electron spectroscopy, Raman, density functional theory (DFT) calculations, etc. The electrochemical analysis of NiCo/pNGr(75: 25) shows an overpotential of approximate to 260 mV at 10 mA cm(-2) with a smaller Tafel slope of approximate to 87 mV dec(-1) and long catalytic durability. DFT calculations are done to check the interaction between the NiCo alloy nanoparticles and the defective sites of pNGr and also with the doped-N, which could be attained for maintaining long catalytic durability. Furthermore, NiCo/pNGr(75: 25) is used as an OER catalyst to fabricate an electrolyzer, which works at very low potential of 1.5 V in 1 M KOH.

Activity tuning of cobalt ferrite nanoparticles anchored on N-doped reduced graphene oxide as a potential oxygen reduction electrocatalyst by Zn substitution in the spinel matrix - Kashyap, Varchaswal; Singh, Santosh K.; Kurungot, Sreekumar (Chemistry Select, 2017)
Development of highly efficient and durable ORR catalysts by using non-platinum group metals (such as Co, Fe, Mn, and Zn) is a challenging task in the forward path towards the realization of low-cost energy devices in the commercial stream. The present work deals with an effective strategy wherein an efficient Pt-free electrocatalyst for oxygen reduction reaction (ORR) is prepared by stoichiometrically substituting some fraction of Fe with Zn in cobalt ferrite and anchoring these spinel nanoparticles on nitrogen doped reduced graphene oxide (N-rGO). Zn substitution is found to be significantly altering the ratio of Fe2+/Fe3+ in the cobalt ferrite nanocrystal system with a concomitant promotional influence on its electrocatalytic activity towards ORR. The nanoparticle composition with a Co, Fe and Zn molar ratio of 1.0:1.7:0.3, represented by the formula CoFe1.7Zn0.3O4(CFZn(0.3)), supported over N-rGO has shown 10 mV and 20 mV positive shift in the onset and half-wave potentials, respectively, for ORR in 0.1 M KOH in comparison to the nanoparticles of CoFe2O4 supported over N-rGO (CF/N-rGO). The optimum Zn substitution is found to be narrowing down the difference with the state-of-the-art Pt/C for ORR by 100 and 110 mV in terms of the onset and half-wave potentials, respectively. Most significantly, the homemade catalyst is found to be clearly outperforming the Pt catalyst in terms of the limiting current density and electrochemical durability.
Keywords: Carbon Nano-fiber; Cathod Catalyst; CoFe2O4; Evolution; Magnetic-properties; Membrane fuel- Cell; Metal-Air Batteries; N-doped graphene; Nanocrystalline; nanocrystals; oxygen reduction reaction; performance; Platinium; solvothermal synthesis; Zn substituted cobalt ferrite

On demand electrochemical release of drugs from porous reduced graphene oxide modified flexible electrodes - Boulahneche, Samia; Jijie, Roxana; Barras, Alexandre; Chekin, Fereshteh; Singh, Santosh K.; Bouckaert, Julie; Medjram, Mohamed Salah; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
Despite the advantages of an electrochemical control for drug release, only a handful of electrochemical-based release systems have been developed so far. We report herein on the development of an electrochemically activatable platform for on-demand delivery of drugs. It is based on flexible gold thin film electrodes coated with porous reduced graphene oxide (prGO) nanosheets onto which the drug of interest has been integrated beforehand. Two different drugs are investigated here: ondansetron hydrochloride (ODS), a selective 5-HT3 receptor antagonist used for preventing nausea and vomiting caused by chemotherapy and radiotherapy, and ampicillin (AMP), an antibiotic to prevent and treat a number of bacterial infections such as respiratory tract infections, urinary tract infections, and meningitis. In the case of ODS, application of a negative potential bias of -0.8 V results in a sustained slow ODS release with an ODS flux of 47 mu g cm(-2) h(-1). In the case of AMP, we show that polyethyleneimine modified prGO (prGO/PEI) is an extremely efficient matrix. Upon the application of +0.8 V, 24% of AMP could be released from the electrical interface in a time span of 2 h. The released AMP kept its antibacterial activity as demonstrated by antimicrobial tests. These examples illustrate the major benefits of the developed approach for biomedical applications.

Efficient and durable oxygen reduction electrocatalyst based on CoMn alloy oxide nanoparticles supported over N-doped porous graphene - Singh, Santosh K.; Kashyap, Varchaswal; Manna, Narugopal; Bhange, Siddheshwar N.; Soni, Roby; Boukherroub, Rabah; Szunerits, Sabine; Kurungot, Sreekurnar (ACS Catalysis, 2017)
Transition metal oxide derived materials are very important for various applications, such as electronics, magnetism, catalysis, electrochemical energy conversion, and storage. Development of efficient and durable catalysts for the oxygen reduction reaction (ORR), an important reaction in fuel cells and metal air batteries, is highly desirable. Moreover, the futuristic catalysts for these applications need to be costeffective in order to ensure a competitive edge for these devices in the energy market. This article describes the synthesis of a cost-effective and efficient electrocatalyst for ORR It is based on supporting CoMn alloy oxide nano particles on N-doped porous graphene through a simple and scalable microwave irradiation method. Microwave irradiation was found to be very crucial for the fast creation of pores in the graphene framework with a concomitant formation of the CoMn alloy oxide nanoparticles. A series of catalysts have been synthesized by varying the Co:Mn ratio, among which, the one with the Co:Mn ratio of 2:1 [designated as CoMn/pNGr(2:1)] displayed remarkably higher ORR activity in 0.1 M KOH solution. It showed a similar to 60 mV potential shift with a low Tafel slope of 74 mV/decade, which is comparable to that derived from the commercial Pt/C catalyst. This high activity of CoMn/pNGr(2:1) has been credited to the cooperative effect arising from the metal entities and the defects present in the N-doped porous graphene. Finally, real system-level validations of the use of CoMn/pNGr(2:1) as cathode catalyst could be performed by fabricating and testing single-cells of an anion-exchange membrane fuel cell (AEMFC) and a primary Zn-air battery, which successfully demonstrated the efficiency of the catalyst to facilitate ORR in real integrated systems of the single-cell assemblies.
Keywords: anion-exchange membrane fuel cell; cooperativity effect; microwave synthesis; oxygen reduction reaction; porous N-doped graphene; Zn-air battery

Magnetic reduced graphene oxide loaded hydrogels: highly versatile and efficient adsorbents for dyes and selective Cr(VI) ions removal - Halouane, Fatima; Oz, Yavuz; Meziane, Dalila; Barras, Alexandre; Juraszek, Jean; Singh, Santosh K.; Kurungot, Sreekumar; Shaw, Pankaj K.; Sanyal, Rana; Boukherroub, Rabah; Sanyal, Amitav; Szunerits, Sabine (Journal of Colloid and Interface Science, 2017)
The formation of composites of reduced graphene oxide (rGO) and magnetic nanoparticles (MP) has flourished in recent years as they combine the advantages of both nanomaterials. Most of these composite materials are prepared by in situ formation of MP onto rGO or by the post-adsorption onto rGO. We report here on a simple and highly controlled method for the fabrication of different magnetic 3D rGO-loaded hydrogels. Cellulose bound magnetic nanoparticles (MP@cellulose) were synthesized by chemical co-precipitation and loaded together with rGO into poly(ethylene glycol) dimethacrylate based hydrogels during their fabrication using photo-polymerization. The magnetic rGO-loaded hydrogels proved to be highly adaptable to different applications. The as-formed composites allowed for efficient dye removal with an adsorption capacity of 111.9 +/- 4 mg g(-1) in the case of methylene blue (MB). Integration of poly(ethyleneimine) (PEI) allowed for the selective capturing of Cr6+ ions with an adsorption capacity of 313 12 mg g-1. Most importantly, independent of the application, the magnetic rGO-loaded hydrogel can be regenerated without loss of its adsorption capacity. (C) 2017 Elsevier Inc. All rights reserved.

Nanocrystalline Fe-Fe2O3 particledeposited N-doped graphene as an activity-modulated Pt-free electrocatalyst for oxygen reduction reaction - Dhavale, Vishal M.; Singh, Santosh K.; Nadeema, Ayasha; Gaikwad, Sachin S.; Kurungot, Sreekumar (Nanoscale, 2017)

Nature of selenium hydrogen bonding: gas phase spectroscopy and quantum chemistry calculations - Mishra, Kamal K.; Singh, Santosh K.; Ghosh, Paulami; Ghosh, Debashree; Das, Aloke (Physical chemistry Chemical physics, 2017)
<div class="block-record-info" style="margin: 0px 22px 22px; list-style: none; padding: 0px; line-height: 20px; font-size: 13px; color: rgb(51, 51, 51); font-family: arial, helvetica, sans-serif; background-color: rgb(248, 248, 248);"> Subsequent to the recent re-definition of hydrogen bonding by the IUPAC committee, there has been a growing search for finding the presence of this ever interesting non-covalent interaction between a hydrogen atom in an X-H group and any other atom in the periodic table. In recent gas phase experiments, it has been observed that hydrogen bonding interactions involving S and Se are of similar strength to those with an O atom. However, there is no clear explanation for the unusual strength of this interaction in the case of hydrogen bond acceptors which are not conventional electronegative atoms. In this work, we have explored the nature of Se hydrogen bonding by studying indole...dimethyl selenide (indmse) and phenol...dimethyl selenide (phdmse) complexes using gas phase IR spectroscopy and quantum chemistry calculations. We have found through various energy decomposition analysis (EDA) methods and natural bond orbital (NBO) calculations that, along with electrostatics and polarization, charge transfer interactions are important to understand Se/S hydrogen bonding and there is a delicate balance between the various interactions that plays the crucial role rather than a single component of the interaction energy. An in-depth understanding of this type of non-covalent interaction has immense significance in biology as amino acids containing S and Se are widely present in proteins and hence hydrogen bonding interactions involving S and Se atoms contribute to the folding of proteins.
Keywords: Center-Dot-O; Clusters; Co-Ordination; Complexes; intermolecular interactions; Proteins; Replacement; spectra; Strength; Sulfur

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. part 1: lysozyme aggregation at pH 2 and 7.4 - Vasilescu, Alina; Boulahneche, Samia; Chekin, Fereshteh; Gaspar, Szilveszter; Medjram, Mohamed Salah; Diagne, Abdou Aziz; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2017)
Protein instability due to misfolding and aggregation is of big concern for protein based therapeutics because it impacts the bioavailability and immunogenicity of such drugs. The development of simple and cost-effective methods for the analysis of pharmaceutical formulations, indicating the presence or absence of protein aggregates, is consequently of high importance. This work proposes a novel electrochemical interface based on porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) allowing for the early and sensitive identification of protein aggregation by following the change in the oxidative current of the proteins. The novelty of this work lies in the exploration of the ability of GC/prGO interfaces to capture different aggregation behaviors. Lysozyme is used as a model to follow by electrochemistry its aggregation at two pH values, pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Comparing the oxidation peak of lysozyme by differential pulse voltammetry (DPV) for different electrode architectures allowed validating the higher sensitivity of the GC/prGO interface versus bare glassy electrodes or electrodes coated with non-porous reduced graphene oxide. Parallel experiments were performed by fluorescence with thioflavin T, size exclusion chromatography and Atomic Force Microscopy (AFM) imaging. These tests further highlighted the usefulness of GC/prGO electrode to visualize in a fast and reliable manner the changes in the protein structure and the differences between the processes occurring at pH 2 and pH 7.4. In particular, the ability to emphasize changes related to the first steps in aggregation that could be indicative of the aggregation course, recommend the GC/prGO electrode in combination with DPV as a new analytical tool for aggregation studies of biopharmaceuticals. Part 2 of this work will demonstrate later the utility of this approach for the analysis of a fast acting injectable human insulin formulation, Humulin R, used for diabetes treatment as well as for calcitonin. (C) 2017 Elsevier Ltd. All rights reserved.

Selective isolation and eradication of E. coli associated with urinary tract infections using anti-fimbrial modified magnetic reduced graphene oxide nanoheaters - Halouane, Fatima; Jijie, Roxana; Meziane, Dalila; Li, Chengnan; Singh, Santosh K.; Bouckaert, Julie; Jurazek, Jean; Kurungot, Sreekumar; Barras, Alexandre; Li, Musen; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
The fast and efficient elimination of pathogenic bacteria from water, food or biological samples such as blood remains a challenging task. Magnetic isolation of bacteria from complex media holds particular promise for water disinfection and other biotechnological applications employing bacteria. When it comes to infectious diseases such as urinary tract infections, the selective removal of the pathogenic species in complex media such as human serum is also of importance. This issue can only be accomplished by adding pathogen specific targeting sites onto the magnetic nanostructures. In this work, we investigate the potential of 2-nitrodopamine modified magnetic particles anchored on reduced graphene oxide (rGO) nanocomposites for rapid capture and efficient elimination of E. coli associated with urinary tract infections (UTIs) from water and serum samples. An optimized magnetic nanocarrier achieves a 99.9% capture efficiency even at E. coli concentrations of 1 x 10(1) cfu mL(-1) in 30 min. In addition, functionalization of the nanostructures with poly(ethylene glycol) modified pyrene units and anti-fimbrial E. coli antibodies allowed specific elimination of E. coli UTI89 from serum samples. Irradiation of the E. coli loaded nanocomposite with a near-infrared laser results in the total ablation of the captured pathogens. This method can be flexibly modified for any other pathogenic bacteria, depending on the antibodies used, and might be an interesting alternative material for a magnetic-based body fluid purification approach.

Interconverting hydrogen-bonding and weak n -> pi* interactions in aqueous solution: A direct spectroscopic evidence - Deb, Pranab; Jin, Geun Young; Singh, Santosh K.; Moon, Juran; Kwon, Hyejin; Das, Aloke; Bagchi, Sayan; Kim, Yung Sam (Journal of Physical Chemistry Letters, 2018)
Molecular structure and function depend on myriad noncovalent interactions. However, the weak and transient nature of noncovalent interactions in solution makes them challenging to study. Information on weak interactions is typically derived from theory and indirect structural data. Solvent fluctuations, not revealed by structure analysis, further complicate the study of these interactions. Using 2D infrared spectroscopy, we show that the strong hydrogen bond and the weak n -> pi* interaction coexist and interconvert in aqueous solution. We found that the kinetics of these interconverting interactions becomes faster with increasing water content. This experimental observation provides a new perspective on the existence of weak noncovalent interactions in aqueous solution.

Nucleic aptamer modified porous reduced graphene oxide/MoS2 based electrodes for viral detection: application to human papillomavirus (HPV) - Chekin, Fereshteh; Bagga, Komal; Subramanian, Palaniappan; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Next to graphene nanomaterials, molybdenum disulfide (MoS2) offers large surface area that can enhance its biosensing performance. In this work, we investigate the performance of glassy carbon (GC) electrodes modified successively with porous reduced graphene oxide (prGO) and molybdenum sulfide (MoS2) for the sensitive and selective detection of the L1-major capsid protein of human papilloma virus (HPV). Owing to the difficulties to perform serological assays and HPV culture efficiently, tools based on molecular recognition are becoming of great importance. We developed here an electrochemical sensor for HPV upon covalent functionalization of the electrode with an aptamer Sc5-c3, a RNA aptamer targeted against the HPV-16 L1 protein. Using differential pulse voltammetry (DPV) and an optimized sensor interface, a linear relationship between the peak current density of a redox couple such as [Fe(CN)6]4- and the concentration of HPV-16 L1 proteins in the range of 0.2-2 ng mL(-1) (3.5 pM-35.3 pM) could be reached with a detection limit of 0.1 ng mL(-1) (1.75 pM). Cross-reactivity studies demonstrated high selectivity over potential interfering species such as HPV-16 E6, opening new opportunities of the developed concept for the development of point of care devices. (C) 2018 Elsevier B.V. All rights reserved.

Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 2: Application to the analysis of calcitonin containing pharmaceutical formulation - Vasilescu, Alina; Ye, Ran; Boulahneche, Samia; Lamraoui, Sabrina; Jijie, Roxana; Medjram, Mohamed Salah; Gaspar, Szilveszter; Singh, Santosh K.; Kurungot, Sreekumar; Melinte, Sorin; Boukherroub, Rabah; Szunerits, Sabine (Electrochimica Acta, 2018)
In part 1 (A. Vasilescu et al., Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 1: Lysozyme aggregation at pH 2 and 7.4 Electrochem. Acta, 254 (2017) 375 -383) we proposed porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) in combination with differential pulse voltammetry as a new analytical tool for aggregation studies of proteins. Lysozyme was used as a model to follow its aggregation by electrochemical means at pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Part 2 of this work widens the scope of this approach by investigating a biopharmaceutical product, as the aggregation of peptide based drugs affects their therapeutic activity and can induce allergic reactions in patients. The salmon polypeptide calcitonin (sCT) was chosen as an example of a bioactive peptide with limited pharmaceutical potential due to a tendency to form cytotoxic aggregates and amyloid fibrils. For practical applications, screen printed electrodes (SPE) and flexible electrodes (FE) modified with polydiallyldimethylammonium (PDDA) and prGO by using the layer-by-layer deposition technique have been developed for the detection of sCT. The results indicate that these electrodes can differentiate between formation of amyloid aggregates of calcitonin (2 mg mL(-1)) in citrate buffer to no aggregation in acetate buffer. It was further demonstrated that these electrodes are able to analyze a pharmaceutical drug product of low potency, Miacalcic (8.3 mu g mL(-1)), where no aggregation was observed. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Calcitonin; Disposable electrodes; Electrochemistry; Porous reduced graphene oxide; Protein aggregation

Repeated photoporation with graphene quantum dots enables homogeneous labeling of live cells with extrinsic markers for fluorescence microscopy - Liu, Jing; Xiong, Ranhua; Brans, Toon; Lippens, Saskia; Parthoens, Eef; Zanacchi, Francesca Cella; Magrassi, Raffaella; Singh, Santosh K.; Kurungot, Sreekumar; Szunerits, Sabine; Bove, Hannelore; Ameloot, Marcel; et al. (Light-Science & Applications, 2018)
In the replacement of genetic probes, there is increasing interest in labeling living cells with high-quality extrinsic labels, which avoid over-expression artifacts and are available in a wide spectral range. This calls for a broadly applicable technology that can deliver such labels unambiguously to the cytosol of living cells. Here, we demonstrate that nanoparticle-sensitized photoporation can be used to this end as an emerging intracellular delivery technique. We replace the traditionally used gold nanoparticles with graphene nanoparticles as photothermal sensitizers to permeabilize the cell membrane upon laser irradiation. We demonstrate that the enhanced thermal stability of graphene quantum dots allows the formation of multiple vapor nanobubbles upon irradiation with short laser pulses, allowing the delivery of a variety of extrinsic cell labels efficiently and homogeneously into live cells. We demonstrate high-quality time-lapse imaging with confocal, total internal reflection fluorescence (TIRF), and Airyscan super-resolution microscopy. As the entire procedure is readily compatible with fluorescence (super resolution) microscopy, photoporation with graphene quantum dots has the potential to become the long-awaited generic platform for controlled intracellular delivery of fluorescent labels for live-cell imaging.

Sensitive electrochemical detection of cardiac troponin I in serum and saliva by nitrogen-doped porous reduced graphene oxide electrode - Chekin, Fereshteh; Vasilescu, Alina; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Iancu, Madalina; Badea, Gabriela; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Cardiovascular diseases pose one of the highest mortality risks among all diseases in developed countries, steadily increasing the burden on the health systems. Early diagnosis of cardiovascular diseases has consequently become highly important to decrease mortality and to use more adapted therapeutic decisions. We demonstrate here the utility of nitrogen-doped reduced graphene oxide (N-prGO) for detecting and quantifying of cardiac troponin I (cTnI), a key human cardiac protein biomarker, under physiologically relevant conditions. Non-covalent modification of N-prGO by 1-pyrenecarboxylic acid (py-COOH) and poly(ethylene glycol) modified pyrene (py-PEG) ligands allowed the covalent integration of Tro4 aptamer, known for its high selectivity towards cTnI. Using differential pulse voltammetry (DPV), a label-free electrochemical sensor for cTnI for concentrations down to 1 pgmL(-1) in human serum could be obtained. This sensitive detection arises from the integration of a porous nanomaterial with excellent electrochemical properties being easily amendable to site-specific surface modification. (C) 2018 Elsevier B.V. All rights reserved.

Substituent‐induced deformed ni–porphyrin as an electrocatalyst for the electrochemical conversion of water into dioxygen - Krishna, J. V. S.; Krishna, Narra Vamsi; Singh, Santosh K.; Shaw, Pankaj K.; Dhavale, Vishal M.; Vardhaman, Anil Kumar; Giribabu, Lingamallu (European Journal of Inorganic Chemistry, 2018)
The electrochemical water oxidation ability of complexes 5,15‐diphenylporphinatonickel(II) (A) and 5,15‐bis(3,5‐di‐tert‐butylphenyl)porphinatonickel(II) (B) in the oxygen evolution reaction (OER) have been investigated in an alkaline medium. Complex B was found to be kinetically and thermodynamically more active than complex A. The overpotential and Tafel slope of complex B are lower than those of complex A by 30 mV and around 45 mV/decade, respectively, which supports the higher activity of B. Moreover, stability tests endorse the sustainability of both samples under alkaline conditions. It has been found that the 3,5‐di‐tert‐butylphenyl substituent in B plays a decisive role in achieving a better OER onset potential and current than that obtained with A, which is a result of the modulation of the structural parameters of B. Furthermore, the measured OER activities of A and B have been correlated with their molecular arrangement as well as differences in their bonding characteristics and dipole moments. For further insight, the obtained results have been confirmed by a theoretical study.

Carbon derived from soft pyrolysis of a covalent organic framework as a support for small-sized RuO2 showing exceptionally low overpotential for oxygen evolution reaction - Chakraborty, Debanjan; Nandi, Shyamapada; Illathvalappil, Rajith; Mullangi, Dinesh; Maity, Rahul; Singh, Santosh K.; Haldar, Sattwick; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (ACS Omega, 2019)
Electrochemical water splitting is the most energy-efficient technique for producing hydrogen and oxygen, the two valuable gases. However, it is limited by the slow kinetics of the anodic oxygen evolution reaction (OER), which can be improved using catalysts. Covalent organic framework (COF)-derived porous carbon can serve as an excellent catalyst support. Here, we report high electrocatalytic activity of two composites, formed by supporting RuO2 on carbon derived from two COFs with closely related structures. These composites catalyze oxygen evolution from alkaline media with overpotentials as low as 210 and 217 mV at 10 mA/cm(2), respectively. The Tafel slopes of these catalysts (65 and 67 mV/dec) indicate fast kinetics compared to commercial RuO2. The observed activity is the highest among all RuO2-based heterogeneous OER catalysts-a touted benchmark OER catalyst. The high catalytic activity arises from the extremely small-sized (similar to 3-4 nm) RuO2 nanoparticles homogeneously dispersed in a micro-mesoporous (BET = 517 m(2)/g) COF-derived carbon. The porous graphenic carbon favors mass transfer, while its N-rich framework anchors the catalytic nanoparticles, making it highly stable and recyclable. Crucially, the soft pyrolysis of the COF enables the formation of porous carbon and simultaneous growth of small RuO2 particles without aggregation.

Graphene-modified electrodes for sensing doxorubicin hydrochloride in human plasma - Chekin, Fereshteh; Myshin, Vladyslav; Ye, Ran; Melinte, Sorin; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Analytical and Bioanalytical Chemistry, 2019)
Doxorubicin (DOX), an anthracycline molecule, is currently one of the most widely used anticancer drugs in clinics. Systematic treatment of patients with DOX is known to be accompanied by several unpleasant side effects due to the toxicity of the drug. Thus, monitoring of DOX concentration in serum samples has become increasingly important to avoid side effects and ensure therapeutic efficiency. In this study, we discuss the construction of a disposable electrochemical sensor for the direct monitoring of DOX in clinical blood samples. The sensor is based on coating a gold electrode in a flexible integrated electrode construct formed on polyimide sheets using photolithography, with nitrogen-doped reduced graphene oxide (N-rGO) suspended in chitosan. Under optimized conditions, a linear relationship between the oxidative peak current and the concentration of DOX in the range of 0.010-15M with a detection limit of 10nM could be achieved. The sensor was adapted to monitor DOX in serum samples of patients under anticancer treatment.
Keywords: Disposable electrodes; doxorubicin; Nitrogen-doped reduced graphene oxide; Serum

NiFe layered double hydroxide-decorated N-doped entangled-graphene framework: a robust water oxidation electrocatalyst - Manna, Narugopal; Ayasha, Nadeema; Singh, Santosh K.; Kurungot, Sreekumar (Nanoscale Advances, 2020)
Three dimensional (3D) porous carbon materials are highly desirable for electrochemical applications owing to their high surface area and porosity. Uniformly distributed porosity in the 3D architecture of carbon support materials allows reactant molecules to access more electrochemically active centres and simultaneously facilitate removal of the product formed during electrochemical reactions. Herein, we have prepared a nitrogen-doped entangled graphene framework (NEGF), decorated with NiFe-LDH nanostructures by an in situ solvothermal method followed by freeze-drying at high vacuum pressure and low temperature. The freeze-drying method helped to prevent the restacking of the graphene sheets and the formation of a high surface area nitrogen-doped entangled graphene framework (NEGF) supported NiFe-LDHs. The incorporation of the NEGF has significantly reduced the overpotential for the electrochemical oxygen evolution reaction (OER) in 1 M KOH solution. This corresponds to an overpotential reduction from 340 mV for NiFe-LDHs to 290 mV for NiFe-LDH/NEGF to reach the benchmark current density of 10 mA cm(-2). The preparation of the catalyst is conceived through a low-temperature scalable process.

Zinc-air batteries catalyzed using Co3O4 nanorod-supported N-doped entangled graphene for oxygen reduction reaction - Manna, Narugopal; Singh, Santosh K.; Kharabe, Geeta Pandurang; Torris, Arun; Kurungot, Sreekumar (ACS Applied Energy Materials, 2021)
The work reported here deals with the development of an efficient non-platinum electrocatalyst for electrochemical oxygen reduction reaction (ORR) through a sequential pathway involving hydrothermal treatment followed by freeze-drying to build the desired structural architecture of the catalyst. The designed catalyst (Co3O4/nitrogen-doped entangled porous 3D graphene (NEGF)), which contains Co3O4 nanorods anchored on the surface of three-dimensional (3D)-structured N-doped graphene, was found to display higher ORR activity during single-electrode testing and demonstrate a Zn-air battery (ZAB) system. Under the hydrothermal treatment at 180 degrees C, in the presence of ammonia, nitrogen was doped into the carbon framework of graphene, which subsequently formed a self-assembled entangled 3D structure of graphene after freeze-drying. The hydrothermal treatment and freeze-drying processes were found to play vital roles in tuning the morphological and structural features of the catalyst. The doped nitrogen, apart from its favorable contribution toward ORR, helped facilitate efficient dispersion of oxide nanorods on graphene. Co3O4/NEGF displayed remarkable ORR activity in 0.1 M KOH solution, as evident from the 60 mV onset potential shift compared to the state-of-the-art Pt/C catalyst and the Tafel slope value of 74 mV dec(-1) vs 68 mV dec(-1) for Pt/C. The ZAB fabricated by employing Co3O4/NEGF as the cathode catalyst was found to be an efficient competitor for the system based on the Pt/C cathode. This high performance has been credited to the controlled interplay of the governing factors such as the interfacial interactions leading to the efficient dispersion of metal oxide nanorods, increased catalyst surface area, the cooperative effect arising from the defects present in the N-doped porous 3D graphene, and the synergetic interactions operating in the system.
Keywords: cobalt-oxide nanorod; freeze-drying; hydrothermal; N-doped entangled graphene; oxygen reduction reaction; zinc-air battery

Air-cathode interface-engineered electrocatalyst for solid-state rechargeable zinc-air batteries - Manna, Narugopal; Singh, Santosh K.; Kurian, Maria; Torris, Arun; Kurungot, Sreekumar (ACS Applied Energy Materials, 2022)
Solid-state rechargeable zinc-air batteries (ZABs) are gaining interest as a class of portable clean energy technology due to their advantages such as high theoretical energy density, intrinsic safety, and low cost. It is expected that an appropriately triple-phase boundary (TPB) engineered, bifunctional oxygen reaction (OER and ORR) electrocatalyst at the air- electrode of ZABs can redefine the performance characteristics of these systems. To explore this possibility, an electrode material consisting of manganese- cobalt-based bimetallic spinel oxide (MnCo2O4)-supported nitrogen-doped entangled graphene (MnCo2O4/NEGF) with multiple active sites responsible for facilitating both OER and ORR has been prepared. The porous 3D graphitic support significantly affects the bifunctional oxygen reaction kinetics and helps the system display a remarkable catalytic performance. The air electrode consisting of the MnCo2O4/NEGF catalyst coated over the gas diffusion layer (GDL) ensures the effective TPB, and this feature works in favor of the rechargeable ZAB system under the charging and discharging modes. As an important structural and functional attribute of the electrocatalyst, the porosity and nitrogen doping in the 3D conducting support play a decisive aspect in controlling the surface wettability (hydrophilicity/hydrophobicity) of the air electrode. The fabricated solid-state rechargeable ZAB device with the developed electrode displayed a maximum peak power density of 202 mW cm(-2), which is significantly improved as compared to the one based on the Pt/C + RuO2 standard catalyst pair (124 mW cm(-2)). The solid-state device which displayed an initial charge-discharge voltage gap of only 0.7 V at 10 mA cm(-2) showed only a small increment of 86 mV after 50 h.
Keywords: air-cathode interface; bifunctional oxygen catalyst; N-doped entangled graphene; solid-state zinc-air battery; spinel oxides

Pseudo-boehmite AlOOH supported NGr composite-based air electrode for mechanically rechargeable Zn-air battery applications - Kharabe, Geeta Pandurang; Manna, Narugopal; Nadeema, Ayasha; Singh, Santosh K.; Mehta, Shweta; Nair, Aathira; Joshi, Kavita; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2022)
Both mechanically and electrically rechargeable zinc-air batteries (ZABs) have received much interest due to their high energy density and suitability for mobile and stationary applications. However, their commercialization has been impeded by the lack of robust, low-cost and environmentally benign catalyst materials that can be easily scaled up. In this context, the present work introduces a new type of transition metal-free catalytic material (AlOOH/NGr) by anchoring the pseudo-boehmite phase of aluminium oxyhydroxide (AlOOH) nanosheets over nitrogen-doped graphene (NGr) via a single-step and straightforward hydrothermal process. Furthermore, density functional theory (DFT) based computation demonstrates that the nucleation of AlOOH starts from the N-sites and points towards the strong surface interaction between AlOOH and NGr via doped nitrogen. AlOOH/NGr consisting of thin layered pseudo-boehmite sheets uniformly distributed over NGr has displayed an oxygen reduction reaction onset potential of 0.83 V and a half-wave potential of 0.72 V, along with good catalytic durability in alkaline medium. With this, AlOOH/NGr, when used as an air electrode for fabricating a primary Zn-air battery, the system has exhibited an open circuit voltage of similar to 1.27 V with a flat discharge profile at a current rate of 10 mA cm(-2). The fabricated system delivered a specific capacity of similar to 720 mA h g(-1) and a high power density of 204 mW cm(-2) and is comparable to the counterpart system based on the state-of-the-art Pt/C (20 wt% Pt) cathode. Additionally, the homemade battery was able to maintain its performance after 4 times of mechanical recharging of the battery, which lasted for more than 35 h at a discharge current density of 10 mA cm(-2). Thus, we have uncovered the potential of an earth-abundant metal-based catalytic system for fabricating and demonstrating a robust mechanically rechargeable zinc-air battery.

Theory-directed designing of an intrinsic-activity-modulated metal-doped copper oxide electrode for nitrate to ammonia synthesis - Tyagi, Nitin Kumar; Mahapatra, Bikash K.; Ghimire, Suvash; Manna, Narugopal; Kumar, Deepak; Kumar, Vijay; Mukhopadhyay, Kausik; Singh, Santosh K. (ACS Applied Energy Materials, 2023)
Synthesis of ammonia via electrochemical reduction ofnitrate isone of the most sustainable routes both for environmental protectionas well as energy saving initiatives. However, this process is limitedto the development of high-performance free-standing catalytic electrodeswith improved selectivity and Faradaic efficiency. Herein, we reporttheory-guided designing and fabrication of free-standing non-noblemetal (Mn, Fe, and Co)-doped copper oxide (CuO) electrodes by usinga simple and scalable electrode preparation method. The density functionaltheory (DFT)-based calculations show that the doped-Co sites in theCu surface facilitate the generation and supply of H+ tothe adsorbed NO3 (-) during the reductionprocess; as a result, the Co-CuO catalyst displays higher selectivitytoward nitrate reduction. The Co-doped Cu electrode (Co-CuO)delivers a higher NH3 yield (5492 mu g cm(-2)) at a reduction potential of -0.91 V vs RHE while maintaininga Faradaic efficiency of >95%. The alloying of Co to the coppermetalnot only facilitates the proton donation to the adsorbed reactant(NO3 (-)) but also tunes the Cu d-center,resulting in the active site modulation responsible for the activationof catalysts.
Keywords: Active sites; ammonia synthesis; electrocatalysis; Faradaic efficiency; High selectivity; metal-doped electrode